Buddhist Visual Cultures, Rhetoric, and Narrative in Late Burmese Wall Paintings. - Green, Alexandra (Hong Kong University Press, 2018)
Step into a Burmese temple built between the late seventeenth and early nineteenth centuries and you are surrounded by a riot of color and imagery. The majority of the highly detailed wall paintings displays Buddhist biographical narratives, inspiring the devotees to follow the Buddha's teachings. Alexandra Green goes one step further to consider the temples and their contents as a whole, arguing that the wall paintings mediate the relationship between the architecture and the main Buddha statues in the temples. This forges a unified space for the devotees to interact with the Buddha and his c.